Pars plana vitrectomy using bimanual technique following intravitreal bevacizumab injection for patients suffering severe proliferative diabetic retinopathy - Aras, Cengiz; Arıcı, Ceyhun; Yolar, Murat (Cerrahpaşa Medical Journal, 2019)
Objectives: To evaluate the anatomic and functional results of pars plana vitrectomy performed with bimanual technique following intravitreal bevacizumab injection in florid type severe PDR patients with intense neovascular vessel and membrane formation. Methods: 14 eyes of 10 patients, in a group of 7 females and 3 males whose ages ranged from 23 and 54, presenting intense neovascular vessel and membrane formation with various degrees of intravitreal haemorrhage were studied. 1.25 mg of 0.05mL bevacizumab injections were performed 3-7 days before surgery. 6 of the 12 phakic eyes were performed fakoemulsification and IOL implantation in the bag just before the surgery. PPV was performed using three-port vitrectomy approach and membranes were peeled with the help of a twinlight chandelier by the bimanual technique. Following aggressive endophotocoagulation, intraocular tampon was inserted (5 eyes C3F8 / 9 eyes silicone oil). Patients were followed up for at least 3 months. Results: 7 patients had preoperative visual acuity of hand movement, 4 patients had a visual acuity of finger counting from 1 meter, 1 patient had a visual acuity of finger counting from 3 meters and 2 patients had a visual acuity of 1/10 respectively. 10 of the patients had a visual acuity measured 5/200 or better after the surgery. (Patients with a pre-operative visual acuity of hand movement were 3/7, and patients with a better visual acuity were 7/7). Anatomic success was achieved in all cases. The cause of failure in patients whom visual acuity did not improve after surgery was attributed to optic atrophy and unfunctionality of large vessels. One of the patients suffered from aggressive rubeosis iridis and neovascular glaucoma postoperatively. Conclusion: Satisfactory anatomic and functional results can be achieved by using bimanual technique and inhibiting neovascularisation in severe PDR patients, whom surgery was avoided and accepted as unsuccessful in recent years because of heavy bleeding and retinal tears.